Opioid overdose death following criminal justice involvement: Linking statewide corrections and hospital databases to detect individuals at highest risk. (1st August 2020) - Krawczyk, Noa; Schneider, Kristin E.; Eisenberg, Matthew D.; Richards, Tom M.; Ferris, Lindsey; Mojtabai, Ramin; Stuart, Elizabeth A.; Casey Lyons, B.; Jackson, Kate; Weiner, Jonathan P.; Saloner, Brendan
Highlights: Justice-involved adults experience high rates of hospitalization and death Encounters with both corrections and hospital systems increases fatal overdose risk Linking corrections and health data can help target overdose prevention efforts Abstract: Background: Persons who interact with criminal justice and hospital systems are particularly vulnerable to negative health outcomes, including overdose. However, the relationship between justice involvement, healthcare utilization and overdose risk is not well-understood. This data linkage study seeks to improve our understanding of the link between different types of justice involvement as well as hospital interaction and risk of fatal opioid overdose among persons with incarcerations, arrests and parole/probation records for drug and property crimes in Maryland. Methods: Maryland statewide criminal justice records were obtained for 2013–2016. Data were linked at the person-level to an all-payer hospitalization database and overdose death records for the same years. Logistic regression was performed to determine which criminal justice and hospital characteristics were associated with greatest risk of overdose death. Results: 89, 591 adults had criminal-justice records and were included in the study. During the 2013–2016 study period, 4108 (4.59 %) were hospitalized for a non-fatal opioid overdose, and 519 (0.58 %) died of opioid overdose. Strongest risk factors for death included being older, being white, having had an inpatient or emergency hospitalization, having had more arrests, having been arrested for a drug charge (vs. property charge), having a misdemeanor drug charge (vs. a felony charge), and having been released from incarceration during the study period. Conclusion: Linking corrections and healthcare information can help advance understanding of risk and target overdose prevention interventions directed at justice-involved individuals with greatest need.